2023
DOI: 10.1021/acsami.2c20270
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication, Properties, and Application of a Printed Green Ag NWs-Based Flexible Electrode and Circuit

Abstract: A suitable conductive ink for office inkjet printers is important for the convenient design of flexible electrodes for triboelectric nanogenerators (TENG). Ag nanowires (Ag NWs) easily printed with an average short length of 1.65 μm were synthesized by using soluble NaCl as a growth regulator and adjusting the amount of chloride ion. The water-based Ag NWs ink with a low solid content of 1% but with low resistivity was produced. The printed flexible Ag NWs-based electrodes/circuits showed excellent conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A brief treatment at 150 °C for 5 min is sufficient to achieve an n-type conductivity of 1 S cm , whereas annealing for 2 h results in a peak conductivity of 8 S cm , providing a solution to the pressing issue of achieving complementary hole and electron transport. Wenxiu Wu et al [ 179 ] has developed high-conductivity inks featuring 1.65 m short Ag NWs with a reduced sintering temperature, by adjusting the reaction rate and lowering the chloride ion concentration using the growth regulator NaCl. Additionally, Ag NWs serve to attenuate the coffee ring effect.…”
Section: Ink-based Tengsmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief treatment at 150 °C for 5 min is sufficient to achieve an n-type conductivity of 1 S cm , whereas annealing for 2 h results in a peak conductivity of 8 S cm , providing a solution to the pressing issue of achieving complementary hole and electron transport. Wenxiu Wu et al [ 179 ] has developed high-conductivity inks featuring 1.65 m short Ag NWs with a reduced sintering temperature, by adjusting the reaction rate and lowering the chloride ion concentration using the growth regulator NaCl. Additionally, Ag NWs serve to attenuate the coffee ring effect.…”
Section: Ink-based Tengsmentioning
confidence: 99%
“…Zhenwei Wang et al [ 228 ] have adeptly fabricated a customizable, fully flexible single-electrode TENG, showcasing its utility as a self-powered tactile sensor (refer to Figure 23 a). Furthering this innovation, Wenxiu Wu and collaborators [ 179 ] utilized high-conductivity ink composed of short Ag NWs to develop a TENG for imbalance detection in robotic systems (refer to Figure 23 b). In a notable endeavor, Ping Sun and co-researchers [ 240 ] leveraged heat-resistant silicone as a fire-resistant and heat-resistant triboelectric negative electrode material, engineering a self-powered multi-arch E-TENG bending sensor and G-TENG pressure sensor.…”
Section: The Latest Advances In Ink-based Nanogenerator Applicationsmentioning
confidence: 99%
“…SPCE provide more possibilities for the study of electrochemical sensors, and sensors with different detection effects can be obtained by modifying different materials. [21][22][23] Paracetamol (PA) is one of the most commonly used antipyretic and analgesic drugs in the medical field, and it is also an excellent free state internal reference probe for constructing a ratiometric sensor in the electrochemical field. 24 It has been reported that it can be synthesized using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ]. Generally speaking, it is necessary to use the second high-temperature sintering (more than 150 °C) step to remove the surface stabilizers and sinter the material into a dense block to form a conductive network; the use of high temperatures that are not conducive to the stability of the fabric substrate will inevitably lead to shrinkage or mechanical problems in the attenuation [ 26 , 27 , 28 ]. To maintain the benefits of textile substrates, it is critical to develop a low-temperature/room temperature sintering technique for activating the conductive network of AgNPs.…”
Section: Introductionmentioning
confidence: 99%